A classification scheme for mixed-species bird flocks - Mangini, Gabriela Giselle (2023)
The literature on mixed-species flocks references a wide variety of bird associations. These studies, however, have used an array of unstructured characteristics to describe flocks, ranging from the temporal occurrence of flocking to the identity and behavioural features of constituent members, with little consensus on which key traits define and characterise a mixed-species flock. Moreover, although most studies report species-specific roles, there is no clear consensus about what these roles signify nor how to define them. This lack of consistency limits our ability to compare flocks from different habitats, regions, and species pools. To unify this sizable body of literature, we reviewed and synthesised 537 studies on mixed-species flocks. We propose 13 categories to classify mixed-species flocks using behavioural and physical traits at the flock and participant level, as well as the habitat where the flock occurs. Lastly, we discuss the historical terminology for different species roles and propose definitions to clarify and distinguish among nuclear, leader, sentinel, and flock-following species. We envision that these guidelines will provide a universal language for mixed-species flock research, paving the way for future comparisons and new insight between different regions and systems.